Forjando-se imaginariamente mulher: um estudo sobre as representações de gênero das jovens no grupo de mulheres do Benguí - BRASIL, Roberta Gilet (Universidade Federal do Pará, 2011)
This work aimed the comprehension of the young gender representations, identifying the social meanings and trying to understand the imaginary positions about being women subjectively. A qualitative methodology was adopted and a participative observation was realized with semi-guided interview in order to obtain the necessary data. Young women from 14 to 18 years living in Benguí (a section of the capital Belem) were interviewed. In a primary socialization, results indicated that the younger internalized some patriarchal values although there were patriarchal and equalitarian meanings of gender coexisting in their representations which were internalized during the secondary socialization with a group of friends and some Jepiara/GMB components. It was reported an empowering social context which contests the patriarchal rules but also being restrictive about women in privacy considering the socio-economic contingencies; a net of subjective and social factors in which the teenagers pretend to be women (adults), singularly reproducing social speech formed during their lives, sketching autonomy on the heteronomy that constitute them as individuals.